Postoperative pain, nausea and vomiting following adeno‐tonsillectomy – a long‐term follow‐up. Issue 8 (13th May 2013) - Stanko, Dana; Bergesio, Ric; Davies, Kylie; Hegarty, Mary; von, Britta S.; Lerman, Jerrold
Summary Background Adenotonsillectomy is a common pediatric surgical procedure. Our knowledge of the recovery profile, parental understanding, and expectations is limited. We aimed to assess the incidence of pain, nausea, and vomiting in children undergoing adenotonsillectomy on postoperative day 3 and 7. We also wished to evaluate parental understanding regarding discharge instructions as well as parental expectations and experience of their child's recovery. Methods We enrolled 100 children (0–16 years) undergoing elective adenotonsillectomy. On day 3 and 7, parents were questioned about their child's level of pain, nausea/vomiting and their understanding regarding postoperative instructions. Results Hundred children (median, 6.68 years) were recruited. 52% of parents rated their child's pain as VAS ≥ 5 on day 3, dropping to 30% by day 7. Almost 33% of patients experienced nausea on day 3, dropping to 11.6% by day 7. A similar trend was observed for postoperative vomiting. Most parents, 89%, agreed that postoperative instructions were clear. However, knowledge regarding when to seek emergency medical advice was found to be lacking. On day 7, only 44% of parents reported that their child's recovery met their expectations. Conclusion Adenotonsillectomy is associated with significant pain and PONV, persisting into the seventh postoperative day. Parental education and information seems inadequate and needs to be improved.